2004
DOI: 10.1029/2003jd003586
|View full text |Cite
|
Sign up to set email alerts
|

Field measurements of water vapor continuum absorption in the visible and near‐infrared

Abstract: [1] We carried out a spectroscopic field experiment designed to measure water vapor continuum absorption in the visible and near-infrared spectral regions. Atmospheric spectra at $1 nm resolution were recorded using direct sunlight at high solar zenith angles during sunrise. Simultaneously radiosonde soundings and a network of geodetic Global Positioning System (GPS) receivers were deployed to constrain the water vapor amount along the absorption path. The solar spectra were analyzed using the Differential Opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 46 publications
0
21
1
1
Order By: Relevance
“…By comparing to narrowband radiometer observations of a narrowband radiometer used in the Atmospheric Radiation Measurement Enhanced Shortwave Experiment (ARESE), Vogelmann et al [1998] found that the CKD continuum (version 2.2) is likely too large in the 950 nm region. This is consistent with the results of Sierk et al [2004], in which spectral atmospheric continuum estimates from direct sun observations were used to conclude that the MT_CKD continuum exhibits a similar spectral shape but a larger magnitude by about 50% in this wavelength region (about 100% for CKD version 2.4.1). Sierk et al [2004] also found that the MT_CKD parameterization underestimates the continuum absorption in the 720 nm band by about 40%, while CKD version 2.4.1 demonstrates good agreement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparing to narrowband radiometer observations of a narrowband radiometer used in the Atmospheric Radiation Measurement Enhanced Shortwave Experiment (ARESE), Vogelmann et al [1998] found that the CKD continuum (version 2.2) is likely too large in the 950 nm region. This is consistent with the results of Sierk et al [2004], in which spectral atmospheric continuum estimates from direct sun observations were used to conclude that the MT_CKD continuum exhibits a similar spectral shape but a larger magnitude by about 50% in this wavelength region (about 100% for CKD version 2.4.1). Sierk et al [2004] also found that the MT_CKD parameterization underestimates the continuum absorption in the 720 nm band by about 40%, while CKD version 2.4.1 demonstrates good agreement.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the results of Sierk et al [2004], in which spectral atmospheric continuum estimates from direct sun observations were used to conclude that the MT_CKD continuum exhibits a similar spectral shape but a larger magnitude by about 50% in this wavelength region (about 100% for CKD version 2.4.1). Sierk et al [2004] also found that the MT_CKD parameterization underestimates the continuum absorption in the 720 nm band by about 40%, while CKD version 2.4.1 demonstrates good agreement. Furthermore, it has been suggested that water dimer absorption may be implicitly included in the CKD continuum model based on laboratory observations between 5,000 and 5,600 cm −1 [ Ptashnik et al , 2004].…”
Section: Introductionmentioning
confidence: 99%
“…The photomorphogenetically active FR spectrum (Borthwick, 1972;Mohr, 1972) corresponds to the 700-740 nm band of water vapour absorption (Robinson, 1966). Moreover, the maximum of the action spectrum in the high irradiance response (HIR) lies at 720 nm (Hartmann, 1966), which coincides with the peak of absorption (Gueymard, 1995;Sierk et al, 2004) in this band (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…Coming to the NIR we note that for this spectral region to our knowledge no atmospheric radiative closure experiments have been reported in the literature with the exception of the studies by Sierk et al (2004) and Mlawer et al (2014). A hindrance for quantitative field studies may have been the fact that absorption in the NIR due to aerosols can become comparable to the magnitude of the water vapor continuum absorption of interest .…”
Section: Introductionmentioning
confidence: 88%